Analisis Peran Guru Dalam Proses Internalisasi Nilai Ta’awun Pada Anak Tunarungu Di SLB B Jati Wiyata Dharma Tuban - Khoriyah, Siti; Silfiyah, Khoirotus; Yusuf Yuwana Arif, Mohammad (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
Deaf children are children who have limitations in hearing and they have the right to education, they are often considered unable to do things like other people do in general. This is also the case for deaf children in SLB B Jati Wiyata Dharma who are often ostracized and underestimated by the community so that an educator figure is needed who is able to direct and develop the contents of the ta'awun values. This study uses a descriptive qualitative approach. Data was collected by means of interview, observation and documentation techniques. Techniques in data analysis include data, data presentation to see the overall picture or certain parts of the research and drawing conclusions to obtain evidence that supports the data collection stage. Based on the research conducted, the following results were obtained: First, The role of the teacher in the process of internalizing ta'awun values ​​including as facilitators, motivators, teachers and learning managers. Second, Supporting factors in the process of internalizing ta'awun values, namely principals' policies, student participation, teacher activity, parental activity, suggestions and infrastructure and programs schools. Third, inhibiting factors for internalizing the value of ta'awun including differences in student understanding, limited number of teachers and environmental factors.